Inhibition of Ca2+/Calmodulin-dependent protein kinase II reverses oxaliplatin-induced mechanical allodynia in Rats - Shirahama Masafumi; Ushio Soichiro; Egashira Nobuaki; Yamamoto Shota; Sada Hikaru; Masuguchi Ken; Kawashiri Takehiro; Oishi Ryozo (SAGE Publishing, 2012)
Abstract Background Oxaliplatin is a key drug in the treatment of colorectal cancer, but it causes severe peripheral neuropathy. We previously reported that oxaliplatin (4 mg/kg, i.p., twice a week) induces mechanical allodynia in the late phase in rats, and that spinal NR2B-containig N-methyl-D-aspartate (NMDA) receptors are involved in the oxaliplatin-induced mechanical allodynia. In the present study, we investigated the involvement of Ca2+/calmodulin dependent protein kinase II (CaMKII), which is a major intracellular protein kinase and is activated by NMDA receptor-mediated Ca2+ influx, in the oxaliplatin-induced mechanical allodynia in rats. Results An increase of CaMKII phosphorylation was found in the spinal cord (L4-6) of oxaliplatin-treated rats. This increased CaMKII phosphorylation was reversed by intrathecal injection of a selective CaMKII inhibitor KN-93 (50 nmol, i.t.) and a selective NR2B antagonist Ro 25-6981 (300 nmol, i.t.). Moreover, acute administration of KN-93 (50 nmol, i.t.) strongly reversed the oxaliplatin-induced mechanical allodynia in von Frey test, while it did not affect the oxaliplatin-induced cold hyperalgesia in acetone test. Similarly, oral administration of trifluoperazine (0.1 and 0.3 mg/kg, p.o.), which is an antipsychotic drug and inhibits calmodulin, reduced both mechanical allodynia and increased CaMKII phosphorylation. On the other hand, trifluoperazine at the effective dose (0.3 mg/kg) had no effect on the paw withdrawal threshold in intact rats. In addition, trifluoperazine at the same dose did not affect the motor coordination in rota-rod test in intact and oxaliplatin-treated rats. Conclusions These results suggest that CaMKII is involved in the oxaliplatin-induced mechanical allodynia, and trifluoperazine may be useful for the treatment of oxaliplatin-induced peripheral neuropathy in clinical setting.